“…And We Are Still Here”: From Berdache to Two-Spirit People - Thomas, Wesley; Jacobs, Sue-Ellen (eScholarship, University of California, 1999)
INTRODUCTION When we gathered people together for two invitational conferences on “Revisiting the ‘North American Berdache’ Empirically and Theoretically,” our aim was to create a dialogue between indigenous/Native people and academics who had written about them. The conferences,funded by the Wenner-Gren Foundation for Anthropological Research, provided the start of collab orative work that took place over the course of five years and resulted in publication of our edited book, Two-Spirit People: Native American Gender Identity, Sexuality, and Spirituality. One of the most important outcomes of the five-year conversation among participants was the realization that the term berdache was no longer acceptable as a catch-all for Native American (indigenous peoples of the United States of America) and First Nations (indigenous peoples of Canada) gender and sexual behaviors. The Native participants concluded that the term was insulting and part of the colonial discourse that continues to be used by select scholars who appropriate indigenous people’s lives in various ways. Native people were talking about this issue long before non-Native academics noticed. The most active resistance to using berdache for sexual and gender diversity in North American aboriginal communities occurred at the Third Annual Native American Gay and Lesbian Gathering, where attendees decided to change the name of their future gatherings to The International Two-Spirit Gathering. At the center of our investigation into the terms we use is a shared determination to reintegrate the word berdache into our respective writings, but using it clearly and precisely in its original meaning: “kept boy” or “male prostitute.” In this paper, we explain our rationale for integrating the use of berdache into our writings about two-spirit people, explore how the self-naming and academic research issues can be accommodated collaboratively, and draw some conclusions about past and future research into Native American sexualities and gender diversity.